Quality improvement of Three-way Catalytic Converter (TWC) system: application of failure modes and effects analysis (FMEA) methodology - Syed Abdul Bahari, Syed Najib; Wan Yusoff, Wan Ahmad Yusmawiza (LAP Lambert Academic Publishing, 2011)
This book intends to present the application of FMEA method on Three-Way Catalytic Converter (TWC) system. Catalytic converter of auto-exhaust emission is one of the most successful applications of heterogeneous catalysis, both in commercial and environmental point of view. Catalytic converter has been proved critical to controlling pollution of CO-HC-NOx caused by automobile sources. TWC system functional lifetime is affected due to catalysts deactivation causes. The study is conducted by using Failure Modes and Effects Analysis (FMEA) method. FMEA method is a systematic and analytical quality planning tool for identifying and addressing what potentially could go wrong with a product or process. It is widely accepted that FMEA is one of the best quality improvement tool. For the last several decades, FMEA has been widely used in industry especially in automotive sectors. It is expected to enhance the lifetime of the TWC by improving its resistance to deactivation. One of practical contributions of this research is to provide guidelines to engineers in monitoring the efficiency of TWC system from the FMEA report.